The Role of English Proficiency in French Language Acquisition: A Case Study of Assassin’s Creed Unity Gamers - Gashmardi, Mahmoud Reza; Yazdian, Amir Reza (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2026)
Language learning methodologies have diversified significantly in recent years, with video games emerging as a prominent technological tool over the past decade. Given the predominance of English as the primary language of interaction in the gaming industry, it can be reasonably assumed that gamers often develop a functional command of English. Furthermore, existing scholarship has extensively documented the linguistic similarities between French and English. This study employs an explanatory research design to investigate the potential influence of English proficiency (minimum B1 level) on French language acquisition among Iranian gamers (N = 18), specifically English undergraduates, addressing the research question: To what extent does prior English proficiency facilitate French language acquisition in a game-based learning environment? Utilizing Assassin’s Creed Unity – a game featuring French as its primary language – the research assessed participants' French comprehension through standardized tests evaluating both written and oral competence. The findings contribute to the growing body of knowledge on cross-linguistic transfer in digital learning environments while simultaneously highlighting the limitations inherent in small-scale studies. Based on the results, the paper proposes recommendations for future research to further explore the efficacy of game-based learning for French as a second language (L2).